Epigenetic dysregulation of key developmental genes in radiation‐induced rat mammary carcinomas. Issue 2 (23rd February 2018) - Daino, Kazuhiro; Nishimura, Mayumi; Imaoka, Tatsuhiko; Takabatake, Masaru; Morioka, Takamitsu; Nishimura, Yukiko; Shimada, Yoshiya; Kakinuma, Shizuko
Abstract : With the increase in the number of long‐term cancer survivors worldwide, there is a growing concern about the risk of secondary cancers induced by radiotherapy. Epigenetic modifications of genes associated with carcinogenesis are attractive targets for the prevention of cancer owing to their reversible nature. To identify genes with possible changes in functionally relevant DNA methylation patterns in mammary carcinomas induced by radiation exposure, we performed microarray‐based global DNA methylation and expression profiling in γ ‐ray‐induced rat mammary carcinomas and normal mammary glands. The gene expression profiling identified dysregulation of developmentally related genes, including the downstream targets of polycomb repressive complex 2 (PRC2) and overexpression of enhancer of zeste homolog 2, a component of PRC2, in the carcinomas. By integrating expression and DNA methylation profiles, we identified ten hypermethylated and three hypomethylated genes that possibly act as tumor‐suppressor genes and oncogenes dysregulated by aberrant DNA methylation; half of these genes encode developmental transcription factors. Bisulfite sequencing and quantitative PCR confirmed the dysregulation of the polycomb‐regulated developmentally related transcription‐factor genes Dmrt2, Hoxa7, Foxb1, Sox17, Lhx8, Gata3 and Runx1 . Silencing of Hoxa7 was further verified by immunohistochemistry. These results suggest that, in radiation‐induced mammary gland carcinomas, PRC2‐mediated aberrant DNA methylation leads to dysregulation of developmentally related transcription‐factor genes. Our findings provide clues to molecular mechanisms linking epigenetic regulation and radiation‐induced breast carcinogenesis and underscore the potential of such epigenetic mechanisms as targets for cancer prevention. Abstract : What's new? Development of a secondary cancer after radiotherapy is of growing concern for long‐term cancer survivors. Here the authors examined epigenetic marks in radiation‐induced rat mammary carcinomas. They found polycomb repressive complex 2‐mediated aberrant DNA methylation of developmentally relevant transcription factor‐encoding genes and a consequent dysregulation of downstream gene targets during carcinogenesis, underscoring the potential of epigenetics in secondary cancer prevention.